2017
DOI: 10.11648/j.sjcm.20170603.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hand Dominance on Functional Status and Recovery of Hand in Stroke Patients

Abstract: Abstract:Stroke is characterized by hemiplegia, including motor deficits and various neurological manifestations mainly in contralateral half of the body lasting more than 24 hours with a presumed vascular cause. The goal of stroke rehabilitation is to make people independent and this is possible with appropriate functioning of the affected hand and upper extremity. Stroke patients have to depend on the nondominant hand when the effected hand is the dominant side. However this disadvantage might end up in bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The participant will be instructed to pick 9 pegs out of a shallow container, 1 by 1, as quickly as possible thereby putting them into 9 holes simultaneously and removing them from the holes to place them back in the shallow container. 25 …”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The participant will be instructed to pick 9 pegs out of a shallow container, 1 by 1, as quickly as possible thereby putting them into 9 holes simultaneously and removing them from the holes to place them back in the shallow container. 25 …”
Section: Secondary Outcomesmentioning
confidence: 99%
“…The variable of hand dominance has been extensively studied in terms of its consequences for physical injuries, cerebrovascular accidents, or other motoric deficits (e.g., Rjosk et al., 2016; Sarikaya, Incel, Yilmaz, Cimen, & Sahin, 2017). In grapho-motoric research, differences between dominant and nondominant hand use have been observed on measures of drawing quality (Zacharias & Kirk, 1998) or completion time (Studenka & Zelaznik, 2008), although other studies have noted similar drawing behaviors between both hands (see Vinter & Meulenbroek, 1993).…”
Section: Role Of Hand Dominancementioning
confidence: 99%
“…BERNHARDT; KWAKKEL, 2011;LIEPERT et al, 1998;SCHAECHTER et al, 2002). RINEHART et al, 2009;SARIKAYA et al, 2017), em nosso trabalho, a adição de AFMD, aumentou a força e a resistência isométrica contra a gravidade na NIHSS.…”
Section: Avaliação Instrumentalunclassified